2009
DOI: 10.1104/pp.109.141408
|View full text |Cite
|
Sign up to set email alerts
|

CYP86B1 Is Required for Very Long Chainω-Hydroxyacid andα,ω-Dicarboxylic Acid Synthesis in Root and Seed Suberin Polyester    

Abstract: Suberin composition of various plants including Arabidopsis (Arabidopsis thaliana) has shown the presence of very long chain fatty acid derivatives C20 in addition to the C16 and C18 series. Phylogenetic studies and plant genome mining have led to the identification of putative aliphatic hydroxylases belonging to the CYP86B subfamily of cytochrome P450 monooxygenases. In Arabidopsis, this subfamily is represented by CYP86B1 and CYP86B2, which share about 45% identity with CYP86A1, a fatty acid v-hydroxylase im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
164
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(174 citation statements)
references
References 64 publications
10
164
0
Order By: Relevance
“…Our results and those of a very recent study (Compagnon et al, 2009) identify CYP86B1 (AT5G23190) as a gene required for suberin verylong-chain a,v-bifunctional monomer synthesis. The ectopic coexpression experiment with GPAT5 and CYP86A1 shows that CYP86A1 produces C16 to C22 monomers in cutin (Li et al, 2007a), while the same experiment with GPAT5 and CYP86B1 shows that CYP86B1 produces C18 to C24 monomers (Fig.…”
Section: Cyp86b1 (At5g23190) Is Required For Very-long-chain Av-bifusupporting
confidence: 68%
See 1 more Smart Citation
“…Our results and those of a very recent study (Compagnon et al, 2009) identify CYP86B1 (AT5G23190) as a gene required for suberin verylong-chain a,v-bifunctional monomer synthesis. The ectopic coexpression experiment with GPAT5 and CYP86A1 shows that CYP86A1 produces C16 to C22 monomers in cutin (Li et al, 2007a), while the same experiment with GPAT5 and CYP86B1 shows that CYP86B1 produces C18 to C24 monomers (Fig.…”
Section: Cyp86b1 (At5g23190) Is Required For Very-long-chain Av-bifusupporting
confidence: 68%
“…However, knockout mutants of these cytochrome P450 genes do not reduce the levels of v-oxidized very-long-chain suberin monomers, so additional cytochrome P450 genes are required for this function. Here, we provide overlapping and additional information to the recent report that the P450 CYP86B1 (AT5G23190) is required for the synthesis of saturated very-long-chain a,v-bifunctional monomers (Compagnon et al, 2009). In addition, although feruloyl transferase activity toward v-OHFAs has been demonstrated in plant extracts (Lotfy et al, 1994(Lotfy et al, , 1996, no genes encoding proteins with this function have been identified thus far.…”
mentioning
confidence: 99%
“…In the case of Arabidopsis the P450 CYP86A2 (ATT1) (20), LACS2 (19,24), and a pair of redundant acyltransferases, GPAT4 and GPAT8 (12), control most of the accumulation of the dicarboxylic acids in leaf and stem cutin, including the dominant yet unusual monomer octadecadiene-1,18-dioic acid. In the case of suberin, a suberin-associated acyltransferase, GPAT5, and two suberin-correlated P450s, CYP86A1 and CYP86B1, are required for the synthesis of suberin-like monomers in cutin of transgenic Arabidopsis (12,(43)(44)(45). This general pattern is now observed with the identification of the acyltransferase GPAT6 and the P450 CYP86A4, which are required for the accumulation of C16 cutin monomers.…”
Section: Discussionmentioning
confidence: 60%
“…The enrichment in the 'suberin' GO term is in agreement with the upregulation in cork oak outer bark of the putative orthologs of wellknown Arabidopsis or potato enzymes with a key role in the biosynthesis of suberin (Table S6A). Specifically, we found upregulation in cork of putative orthologs to the Arabidopsis GPAT5, CYP86A1, CYP86B1 and AtHHT/ASFT, and of putative orthologs to the potato CYP86A33 and FHT Li et al 2007;Höfer et al 2008;Serra et al 2009Serra et al , 2010Compagnon et al 2009;Gou et al 2009;Molina et al 2009). Aside from suberin, phellem imperviousness has been attributed to the associated waxes, which in cork consist mainly of isoprenoids such as triterpenes and sterols (Castola et al 2005).…”
Section: Discussionmentioning
confidence: 85%